2019
DOI: 10.1016/j.pmrj.2018.08.377
|View full text |Cite
|
Sign up to set email alerts
|

A Single Trial May Be Used for Measuring Muscle Strength With Dynamometers in Individuals With Stroke: A Cross‐Sectional Study

Abstract: Level II, prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…All strength measurements were taken with the participants lying in the supine position, following previously described protocols (Dorsch et al., 2012). Only one trial has shown to be required to provide consistent and reliable results (Aguiar et al., 2018). A composite score for the LE was calculated, by adding the strength values of the tested muscular groups.…”
Section: Methodsmentioning
confidence: 99%
“…All strength measurements were taken with the participants lying in the supine position, following previously described protocols (Dorsch et al., 2012). Only one trial has shown to be required to provide consistent and reliable results (Aguiar et al., 2018). A composite score for the LE was calculated, by adding the strength values of the tested muscular groups.…”
Section: Methodsmentioning
confidence: 99%